Statistical Modeling of the Impact of Major Insect Pests of Watermelon on its Agronomic Performance: Linear Regression Perspective - Okrikata, Emmanuel; Ogunwolu, Emmanuel Oludele; Odiaka, Ngozi Ifeoma (International Journal of Scientific Research in Biological Sciences, 2019)
Studies on the impact of major pests of watermelon on its agronomic performance are hard to find. This paper presents the relationship between the agronomic performance of watermelon and density of its major insect pests with the aid of correlation and linear regression models using data collected from forty (40 m2) plots grouped into 4 replicates (10 plots/replicate) in field experiments in the early- and late-sown crop of 2016 and 2017 in the Research Farm of Federal University, Wukari, Nigeria. Plant survival rate (%) negatively and significantly (P < 0.05) correlated with each of mean number leaf-feeding beetles, A. gossypii density and B tabaci density in both the early- and late-sown crops of 2016, respectively; with a similar trend in 2017. All parameters significantly (P < 0.05) fitted the linear regression model. Densities of all major pests consistently correlated negatively and significantly with fruit yield. Student’s t-test detected significant differences between the pest and agronomic characters of the early- and late-sown crops of both years. We therefore conclude that watermelon experiences multiple pest infestations whose compositions and intensities vary between seasons and that, their influence on agronomic performance as shown by the coefficient of determination (R2) values (which were indicative of the effect of pests on crop performance) were largely > 50 %. Lower pest infestation (frequency and intensity) was also empirically shown to give rise to better growth indices and higher yields.